Perencanaan Sistem Penyaliran Tambang Batubara Bawah Tanah Seam C1 Blok Timur Site Sapan Dalam PT Nusa Alam Lestari Desa Salak, Sapan Dalam, Kota Sawahlunto, Sumatera Barat - Stella Putri Pratama; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT Nusa Alam Lestari in July 2018 on the mining front of the Seam C1 hole carried out mining activities along the 97 meter opening hole in the main hole and 4 branch holes that had been realized. The amount of groundwater discharge entering the mining area at the Seam C1 hole is 5.112 m3 / minute. The number and specifications of the ideal pump for pumping water from the Seam C1 pit mine front are 2 units of Airlux pump with a discharge capacity of 6 m3 / hour in operation, with an Airlux pump with a discharge capacity of 6 m3 / hour with a maximum head of 12 meter; the actual total head is 25.08 m on front of Seam C1. The dimensions and shape of the sump design are ideal for underground coal mine drainage systems at the Seam C1 mining site planned to be rectangular with dimensions of 2 m in length, 1 m in width, 2 m in depth. Keywords: Underground Mine, Mine Dewatering, Groundwater Discharge, Pump, Sump